Discussion on importance of e⁺e⁻ pair emission in the ¹²C(α, γ)¹⁶O capture reaction below 1.9 MeV energy - Tabassam, U.; Mehboob, K. (Вопросы атомной науки и техники, 2015)
The cross section of the direct E0 pair emission has meaningful contribution to the total cross section of the ¹²C(α, γ)¹⁶O reaction at low energy ≤ 1:9MeV . E0 resonance emission and internal pair conversion have significant effect to the total cross section of the ¹²C(α, γ)¹⁶O reaction. In this paper e⁺e⁻ paired emission has been focused on taking into account the angular correlation. E0 contribution is also significant in a presence of E1 and E2 transition, therefore e⁺e⁻ pair emission may not be neglected and has a signi cant effect on the total cross section in the case of the ¹²C(α, γ)¹⁶O reaction.